1 - Leçons de la pandémie : science, religion et citoyenneté mondiale, - Diagne, Souleymane Bachir (Africa Development, 2024)
*Revised Text of the Endnote Lecture delievered at the 16th CODESRIA General Assembly held from 4th to 8th December 2023. Each and every one of us has experienced the pandemic in a personal, intimate way, but it also holds universal lessons, and the time has come for us specialists in the social sciences and humanities to start drawing lessons from what happened to us when the corona virus broke into the world. As my contribution to this process – which, as always, CODESRIA is absolutely right to consider urgent and necessary – I am going to share with you some of the thoughts I have expressed publicly during the two alarming years in which the virus has been on the rampage, on subjects such as citizenship and religion in the face of the health crisis, the discourse of science in the face of the Covid-19 challenge, and the case for a ‘(cosmo)politics of humanity’ in response to the health crisis and the climate emergency. These speeches were given at academic conferences, of course, but also in press interviews when, like many others, I was asked to comment on these subjects because of my work in Islamic philosophy on